Enhancing Students’ Reading Achievement by Using Reading Strategy Based Instruction (RSBI) Method - nurul afidah (JoEMS (Journal of Education and Management Studies), 2019)
The purpose of this study is to improve students’ reading ability through RSBI (reading Strategy Based Instruction) method. After implementing the strategies in three meetings, test was administered, and the result of the test was 67 which was below the criteria of success, so that the next cycle is needed. On the second cycle some steps are revised, such as time of applying the strategies is more than time of lecturing. The result of the second test was 78 so that the research can be stopped in the second cycle Since it was classroom action research (CAR), further researchers could conducted experimental as research design so they could compare the effectiveness RSBI with another media. Or conduct similar study by different population, grade or, skill.